Digital Strain at Work: Technostress, Work Engagement, and Burnout among Public Sector Employees - Wildan Vanny Hashona; Elok Savitri Pusparini (UNIVED Press, 2026)
The increasing reliance on Information and Communication Technology (ICT) has transformed how public sector institutions operate, creating not only improvement but also new challenges for employees. This study investigates the impact of technostress on employee well-being using the Job Demand–Resource (JD-R) framework. Data was collected from 364 auditors at The Financial and Development Supervisory Board (BPKP) through a non-probability sampling and analyzed using SmartPLS. The findings reveal that technostress creators significantly increase burnout and reduce work engagement, while technostress inhibitors mitigate these effects by reducing burnout and enhancing work engagement. The study further confirms the mediating role of work engagement in the relationship between technostress and burnout, highlighting its importance as a psychological resource. Unlike previous research, which predominantly focused on healthcare and academic professionals, this study provides new insight into the effects within the public sector context, particularly among auditors in Indonesia. The findings offer practical implications for improving employee well-being through better digital support systems.